Surgical Resection of Tracheal Diverticulum with Haemoptysis as Unusual Presentation - Leonardo Toscano; Daniel Terra; Siul Salisbury; Nicolas Arechavaleta (Case Reports in Surgery)
Tracheal diverticulum is defined as an air cyst located on the lateral wall, congenital or acquired. Most of them are asymptomatic, incidentally found on CT. The common symptoms are chronic cough, stridor, or recurrent respiratory infections. Asymptomatic diverticulum requires no treatment and managed conservatively while surgical excision is indicated in cases of local complications or symptom permanence. We report a case of tracheal diverticulum presented with haemoptysis, a rare symptom. The diagnosis was made with a CT that shows a 15 mm air image on the right lateral trachea wall. Due to symptoms’ persistence, we decide to perform surgery with a good outcome.